Socioeconomic Context, Pedagogical Practice and Autonomous Learning in the Classroom [Contexto Socioeconómico, Práctica Pedagógica y Aprendizaje Autónomo en el Aula] - Villalta-Paucar, M (Universidad Austral de Chile, 2018)
The aim of this research was to analyze the effective pedagogical practice for the achievement of autonomous learning in different socio-educational contexts of Elementary Education. Methodology consisted of a descriptive study of the classes of eight teachers, 16 executives and 40 children of first and second grade from four schools of the Metropolitan Region, Chile, selected according to their socioeconomic status (SES) and academic achievement measured by the test of the Education Quality Measurement System (SIMCE). Classes and interviews were recorded. Conversation Analysis (CA), criteria for the Mediated Learning Experience (MLE), nonparametric statistics, and semantic content were analyzed. Findings suggest that the classroom pedagogical practices are different according to the SES and academic achievement. The effectiveness to promote autonomous learning is focused on the placement or cultural enrichment according to students socioeconomic status. © 2018, Universidad Austral de Chile.; El objetivo fue analizar la práctica pedagógica efectiva para el logro de aprendizaje autónomo en diferentes contextos socioeducativos de Educación Básica. Metodológicamente es un estudio descriptivo de las clases de ocho profesoras, 16 directivos y 40 niños de primero y segundo básico, de cuatro escuelas de la Región Metropolitana de Santiago de Chile, seleccionadas según nivel socioeconómico (NSE) y logro escolar medido por la prueba del Sistema de Medición de la Calidad de la Educación (SIMCE). Se hizo registro fílmico de las clases y entrevistas. Se realizó análisis de la Conversación (AC), de criterios de Experiencia de Aprendizaje Mediado (EAM), estadística no paramétrica, y análisis de contenido semántico. Los resultados indican que las prácticas pedagógicas de aula son diferentes según el NSE y el logro escolar. La eficacia para promover aprendizajes autónomos se orienta a la nivelación o de enriquecimiento cultural según sea el nivel socioeconómico de los alumnos. © 2018, Universidad Austral de Chile.